Pengaruh Harga Dan Lokasi Terhadap Keputusan Pembelian Pada Fore Coffe Cirebon - Muangsal; Kurniawan, Rudi (POLITEKNIK LP3I, 2025)
The purpose of this research is to analyze how price and location affect consumer purchasing decisions at Fore Coffee Cirebon by employing a quantitative methodological approach. A total of 100 respondents were selected through a non-probability sampling technique. The variables were assessed through a Likert-scale instrument, and the collected data were subsequently analyzed with SPSS version 22. The analysis process involved conducting validity tests, reliability assessments, multiple linear regression evaluations, and partial t-test examinations, simultaneous F-tests, and the coefficient of determination (R²). The results indicate that both price and location significantly affect consumer purchasing decisions, with price emerging as the most significant contributing factor. Overall, the research model accounts for 48.5% of the variation in purchasing decisions, while the remaining 51.5% is explained by other variables not examined in this study